GENEL İLE ÖZEL ARASINDA OSMANLI TASNÎFU’L-ULÛM LITERATÜRÜNE GİRİŞ - (:unkn) unknown (My University, 2019)
Taşköprülüzâde Miftâhu’s-seâde ve misbâhu’s-siyâde adlı eserinde ilmu tekâsîmi’l-ulûm başlığı altında, bu ilim dalının “en genel konudan en özel konuya tedricî inişi” araştırdığını belirterek, bu araştırmayla, herhangi bir ilim dalının münderic olduğu daha genelin tespit edilebileceğini belirtir. Bu ilke çerçevesinde konusu bakımından en genel ilim metafizik(el-ilmu’l-ilâhî) olduğundan tüm diğer ilimler onun furûu olarak ‘taksîm’ edilir; ancak bu hareket noktası açısından sıra düzeni(tederruc) “en özelden en genele” ya da “en genelden en özele”, iki farklı biçimde yapılabilir. Bu çalışmada Taşköprülüzâde’nin tasnîfu’l-ulûm bilim dalı için koyduğu bu ilkeye bağlı kalınarak, Osmanlı tarihi boyunca geneli ve özeli konu alan ilim sınıflandırmalarına ilişkin yaygın literatürde bilinen eserler tespit edilecek, kısaca incelenecek ve çözümlenecektir.

In his works Miftâh as-saâda wa misbâh as-siyâda under the title ilm taqâsim al-ulûm, by explaining this science as a research of “gradual descend from the most general subject to the most specific” Tashkopruluzâdah remarks that any science can be deducted as a part of a broader general. Within this principle, because the most general science in respect to its topic is metaphysics, all other sciences are divided as its branches. This is done by two different ways in the light of the alignment point “from the most specific to the most general” or “from the most general to the most specific”. In this article, abiding by this principle appointed by Tashkopruluzâdah for the science of tasnîfu’l-ulûm, the works concerning the classification of sciences which issue the general or the specific throughout Ottoman history will be detected, examined and analyzed.
INTRODUCTION TO THE OTTOMAN LITERATURE OF THE CLASSIFICATION OF SCIENCES BETWEEN THE GENERAL AND THE PARTICULAR